Ship Recycling Rig Hibiscus Ditinjau Dari Sistem Manajemen Daur Ulang Ramah Lingkungan - Mufti Fathonah Muvariz; Benny Haddli Irawan; Aziz Nur Rahman; Lalu Giat Juangsa Putra (Politeknik Negeri Batam, 2023)
Ship recycling is considered the best alternative for disposing of obsolete ships. Ship recycling is an activity related to the ship recycling process, such as mooring/grounding of ships, taking, and repairing ship materials. The existence of the ship recycling industry in Indonesia includes Tanjung Jati (Madura), Cilincing (North Jakarta), Tenggamus (Lampung) and Tanjung Uncang (Batam). This study aims to determine the process of ship recycling hibiscus rigs carried out at PT. Batam Citra International, Tanjung Uncang, Batam City. Based on the results of the research conducted, it was found that the ship recycling rig hibiscus process was carried out using a cutting plan work plan, with the following stages: (1) Pre-arrival process at Sekupang anchorage, (2) Customs inspection at Sekupang Port, (3) Ship towed from Sekupang Harbor to PT. BES ship berths, (4) General inspection by PT. BCI and PT. BES, (5) Inspection by local environmental agencies, (6) Marking of IHM/dangerous substances on ships, (7) Transfer of hazardous and non-hazardous materials on board, (8) Transfer of oil and other flammable goods, (9) Engine room cleaning, (10) Ship recycling starts, (11) Monthly review of hazardous waste disposal, (12) Review of incidents that occurred and precautions taken, (13) Results of ship recycling, and finally, and (14) Compilation of ship recycling compliance reports.